Modelling farmers’ marketing processes :|the case of the potato sector in Turkey’s Çorum province - Yıldıran, Safa. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
Many reports and calculations regarding the share of each actor in the final price of agricultural products show that there exists a downward pressure on producer prices. Even if a substantial body of the studies on the Turkish agricultural sector discusses the marketing channels of the producers and states reasons for the low producer prices, they do not construct theoretical models. Other studies consisting of theoretical models are generally conducted in the underdeveloped regions and focus on the effect of price information on the producer prices. This study provides a bargaining model within the two-stage optimization problem of potato producers in Çorum province who sell their products to both traders and the firms based on the information gathered from the interview with 35 potato producers, four traders, two municipal policemen and a manager of the wholesale market. The study aims to find out possible reasons for the downwardly pressured producer prices. According to the results of the model, the difference in the behaviors of familiar and unfamiliar traders regarding the payment process makes the producers dependent on their network and decreases the prices they demand during the bargain to not lose the familiar traders. Also, the model shows that the producer can increase the price he demands by 37.5% in response to a 40% increase in the lower bound of the prices if the average price demanded by other producers increases simultaneously. In the case of a lack of joint action, the response of the producer remains limited at 15%.
Keywords: Potato industry -- Çorum -- Turkey.; Farm produce -- Turkey -- Marketing.